Reimagining English Learning: Technology in Material Design for Secondary Education - Yu, Yanshen; Huang, Xuefang; Li, Peijun; Lin, Qingzu; Tang, Jintian (Journal of Educational Research and Policies, 2024)
As classrooms move towards a digital landscape, a key factor for successful English language education is to create and apply new experience in teaching materials. This study investigates the impact of technology integration on English teaching material design in secondary education, unveiling the significant role of teachers' pedagogical expertise. Qualitative data, derived from semi-structured interviews, field notes, and teaching documents, were collected and analyzed, revealing that technology, when guided by pedagogical principles like Activity Theory, TBLT, Constructivism and Cognitive Load Theory, can enhance student engagement and language learning. The findings also suggest teachers’ evolving roles, from instructors to facilitators and tech integrators, significantly transform the classroom dynamics. The study highlights the need for robust supporting systems, including professional development and infrastructure, which can ensure effective tech integration. It concludes that with the right support and pedagogical understanding, technology can navigate English education into a more dynamic and student-centered experience.